2018
DOI: 10.1159/000490242
|View full text |Cite
|
Sign up to set email alerts
|

Nomograms of the Fetal Sylvian Fissure and Insular Lobe throughout Gestation: A Multicentric, Ultrasonographic Cross-Sectional Study

Abstract: Introduction: Anomalies in cortical development are often associated with an adverse outcome, but prenatal diagnosis is often impeded by the limited knowledge about normal sulci biometries throughout fetal brain development. Our aim was to provide two-dimensional ultrasonographical (2D US) nomograms of the depth of the Sylvian fissure (SF) and insular lobe (IL), as well as of the SF ratio throughout gestation in a large number of fetuses. Materials and Methods: This was a prospective cross-sectional study of 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 28 publications
0
8
0
Order By: Relevance
“…Excluded studies and reasons for exclusion are reported in Table S3 . Finally, 42 studies, reported between January 1970 and 2021, met the inclusion criteria, and these provided data for 45,626 fetuses, included in the final analysis ( Table 1 ) [ 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 ]. The median sample size of participating fetuses was 372.5 (range: 50 to 8313; 25th percentile: 175.8; 75th percentile: 709.3).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Excluded studies and reasons for exclusion are reported in Table S3 . Finally, 42 studies, reported between January 1970 and 2021, met the inclusion criteria, and these provided data for 45,626 fetuses, included in the final analysis ( Table 1 ) [ 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 ]. The median sample size of participating fetuses was 372.5 (range: 50 to 8313; 25th percentile: 175.8; 75th percentile: 709.3).…”
Section: Resultsmentioning
confidence: 99%
“…Nine studies reported more than one fetal brain structure [ 9 , 10 , 17 , 32 , 34 , 36 , 41 , 42 , 43 ]. In addition, 4 studies reported charts for POF [ 9 , 10 , 17 , 36 ], 6 for SF [ 9 , 10 , 17 , 35 , 36 , 44 ], 3 for AV [ 22 , 36 , 43 ], 14 for PV [ 7 , 8 , 14 , 19 , 23 , 26 , 27 , 30 , 32 , 34 , 36 , 38 , 40 , 43 ], 20 for TCD [ 12 , 15 , 16 , 18 , 20 , 21 , 24 , 25 , 28 , 31 , 32 , 34 , 39 , 41 , 42 , 43 , 45 ,…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The parahippocampal gyrus is located at the bottom of the lateral groove, and the surrounding round groove is separated from the frontal lobe, temporal lobe, and head lobe. The function may have visceral autonomic nerve and Guam leaf damage, which may cause emotional instability, language disorder, hallucinations, and other mental symptoms [25]. According to the fMRI study, an AlFF increase on both sides of the bipolar disorder, down to both sides of the bipolar disorder, extending to the body of the body, right SFGmed and right superior temporal gyrus (STG) [26].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Poon et al 1 and Pooh et al 2 published interesting studies on an objective approach to analyze the operculization of the Sylvian fissure (SF) based on transvaginal coronal sections at 18-30 weeks of gestation. These studies were an extension of previously published reports 3,4 which aimed to help imaging physicians in screening for and/or the diagnosis of cerebral or cortical anomalies, using an objective approach based on anatomical structural measurements.…”
mentioning
confidence: 98%